Nobility Reimagined : The Patriotic Nation in Eighteenth-Century France - Smith, Jay M., 1961- (Book collections on Project MUSE., 2005)
Smith argues that the attempt to redefine and restore French nobility brought forth competing visions of patriotism with correlating models of the social and political order. Although the terms of public debate have changed, the same basic challenge continues to animate contemporary politics.